The relation between renal failure and kidney function parameters, packed cell volume and blood pressure - Ali Ibrahim Mohammed Alsamawi (World Journal of Experimental Biosciences, 2016)
This study was conducted to find out the relationship between renal failure and kidney function parameters like blood urea, blood sugar, blood pressure, serum phosphate, and packed cell volume (PCV) %. Eight three subjects aged from 22 to 75 years old (53 males and 30 females), this study extended from December 2015 till April 2016. Sixty-three patients were suffering from renal failure while other twenty were non infected and considered as control group. Blood urea, blood sugar, blood pressure, serum phospharous level were assayed using biochemical function tests, PCV% level was assayed using hematological test. It was found significant increase in blood urea, serum phospharous (P < 0.05) in the patients compared with control group, and significant decrease in PCV% (P < 0.05) in infected subjects as compared with non-infected group. In contrast, it was observed no significant difference between infected and non-infected individuals in terms of level of blood sugar (P > 0.74).
Keywords: Blood pressure, Kidney function tests, Packed cell, Renal failure.